2011
DOI: 10.1007/s10165-011-0515-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of 405 Japanese patients with systemic sclerosis

Abstract: We aimed to clarify the clinical features of Japanese patients with systemic sclerosis (SSc), especially with reference to organ involvement and autoantibodies. A cohort of 405 patients with SSc who attended our institution from 1973 to 2008 was identified retrospectively. Data on clinical features, including autoantibodies, organ involvement, and overlap of other connective tissue diseases, were obtained by following the medical records until 2009. The percentage of male patients during or after 1990 was grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 25 publications
(37 reference statements)
2
15
4
Order By: Relevance
“…ATA is reported as a SSc‐specific antibody, particularly in the dcSSc subset . Our study revealed that the presence of ATA was strongly associated with pure scleroderma and the finding was supported by our subgroup analysis.…”
Section: Discussionsupporting
confidence: 86%
“…ATA is reported as a SSc‐specific antibody, particularly in the dcSSc subset . Our study revealed that the presence of ATA was strongly associated with pure scleroderma and the finding was supported by our subgroup analysis.…”
Section: Discussionsupporting
confidence: 86%
“…However, the phenotypes of SSc appeared to be different in various regions of Asia. Studies in West Malaysia, India and Japan have reported more cases of lcSSc . In contrast, dcSS appears to be more commonly reported in East Malaysia, similar to the findings in Thailand, Singapore, Taiwan and China .…”
Section: Discussionsupporting
confidence: 73%
“…There was a high prevalence of ATA positivity in our SSc patients (85%) compared to previous studies on Caucasians (13–50%), African‐Americans (31%) and other Asian populations (11–70%) . This might be explained by the high prevalence of the dcSSc subset among Thai SSc patients against some Asian and Western series, perhaps because of ethnic differences or genetic factors .…”
Section: Discussioncontrasting
confidence: 56%
“…Anti‐U1‐RNP and anti‐PM‐Scl autoantibodies associated with SSc overlap with other connective tissue diseases, are reportedly associated with the lcSSc subset . Anti‐U1‐RNP was identified as a co‐existing antibody with ATA in a study which included SSc overlap with other connective tissue diseases . According to our study, there was no association between the presentation of ATA and the SSc subset after excluding SSc overlap with other connective tissue diseases.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation